The expression 5(4) - 6 + 5(4) - 6 is equivalent to (k + k)(4) option fourth is correct.
It is defined as the combination of constants and variables with mathematical operators.
The question is incomplete.
The complete question is:
If k(x) = 5x – 6, which expression is equivalent to (k + k)(4)?
Plug k = 4 in the function:
k(4) = 5(4) - 6
Now,
= (k + k)(4) or
= k(4) + k(4)
= 5(4) - 6 + 5(4) - 6
Thus, the expression 5(4) - 6 + 5(4) - 6 is equivalent to (k + k)(4) option fourth is correct.
Learn more about the expression here:
brainly.com/question/14083225
#SPJ1